Domestic support to agriculture in the European Union and the United States: policy developments since 1996 - Gopinath, Munisamy; Mullen, Kathleen; Gulati, Ashok (International Food Policy Research Institute, 2004)
In this study, we outline the farm policy changes in the European Union, EU, and the United States, US, since 1996 and compare their levels of support under various policies. The producer support estimates for the EU are more than twice that of the US, although the value of EU agricultural production is only 30% more than the US production value. In the EU, reductions in the intervention (support) prices for cereals, oilseeds and beef sector have been compensated by increased direct payments, i.e., payments based on historical acreage and yield or animal head counts. In 1996, the US eliminated target prices and deficiency payments for major crops, and acreage set-sides for supply control. They have been replaced with fixed and emergency payments. However price floors (loan rate with deficiency payments) have been retained for major crops. The sugar and dairy sector policies of the EU and the US have undergone few changes since 1996....The initial EU and US agricultural proposals for the Doha round focused on reducing market access barriers and export subsidies, but refrained from limiting domestic support measures. Developing countries’ effective opposition to these proposals led to the collapse of the 2003 WTO Ministerial Meeting at Cancun, Mexico. The recently announced Doha Work Program proposes complete elimination of export subsidies and significant reductions in market access barriers. In the case of domestic support, developing countries’ views such as the reductions in product and non-product specific de minimis provisions, and the criteria for blue box payments are reflected in the proposal. At the same time, developed countries’ views on the continued placement of direct payments in either blue or green box have been included in the proposal. However, agreement on the extent of reductions and the specific modalities is expected in the next 16 months. The final agreement, scheduled for presentation to members at the Hong Kong WTO Ministerial Conference in December 2005, likely depends on whether or not the new proposals and their modalities would result in meaningful limits on domestic support.